A Quantitative Study to Determine the Motivations, Perceptions, And Behaviours of Participants in the Adana Orange Blossom Carnival - ÇUHADAR, MURAT; ÇELİK ÇAYLAK, PINAR and TOPSAKAL, YUNUS (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The study focuses on the motivations, perceptions, and behaviours of participants in the Adana Orange Blossom Carnival. The data was collected from 339 participants who did not reside in Adana but attended the carnival. The research was conducted using a quantitative research method, and the data was collected through a questionnaire. The questionnaire included statements about the reasons for attending the Adana Orange Blossom Carnival, its attractiveness, decision-making factors, satisfaction, behavioural intentions, and social media usage. It was found that the majority of participants attended the carnival as a social event with their friends or family. It was concluded that participants attended the event to have fun, spend enjoyable time with friends, gain experiences, and relieve stress. According to the findings, female find the carnival less attractive than male but have a higher perception of attending for the purpose of enjoyment. Another finding is that social media influences the decision to participate in the carnival. Participants believe that they are happy to attend the carnival and that their expectations are met. The findings demonstrate the significance of social media platforms as an important factor in contemporary event participation.